Shoot the Rehearsal!: Behind the Scenes with Assistant Director Reggie Callow - Behlmer, Rudy (Rowman & Littlefield Publishers, 2010)
Ridgeway (Reggie) Callow began his film career in the early 1930s and for four decades worked as an assistant director on some of the most memorable films in Hollywood history. In the early 1970s, over a period of several months, film historian Rudy Behlmer conducted interviews with Callow, and the result is this edited version of many hours of relatively informal conversations recorded between the two men. In these extracts, Callow recounts what it was like to work on such celebrated films as Gone with the Wind, Rebecca, Mutiny on the Bounty, and The Sound of Music, recalling the work of filmmakers Alfred Hitchcock, Howard Hughes, David O. Selznick, Michael Curtiz, John Huston, Carol Reed, Lewis Milestone, and Robert Wise. Callow also provides first-hand knowledge and inside information about stars of the period, including Clark Gable, Humphrey Bogart, Spencer Tracy, Grace Kelly, James Cagney, Elizabeth Taylor, Bette Davis, Marlon Brando, Julie Andrews, and others. Callow does not romanticize the glamour of Hollywood or echo carefully nurtured myths of legendary pioneer creative figures but rather recounts the workaday world of film business with revelations about major productions and personalities.